Analysis of the Impact of Reward Provision on Science Learning Interest among Fifth-Grade Students at SDN 22 Jeppe’e, Tanete Riattang Barat District, Bone Regency - Muliadi; Sudarto; Ajrun Karim (PT. Lontara Digitech Indonesia, 2025)
This study is a descriptive qualitative study that aims to determine the impact of reward provision on science learning interest among fifthgrade students at SDN 22 Jeppe’e. The focus of this study includes an overview of science learning and the impact of reward provision on students’ learning interest. The subjects of the study were the teacher and fifth-grade students at SDN 22 Jeppe’e. Data collection techniques included interviews, observation, and questionnaires. The results showed that science learning was implemented well, with an average student questionnaire score of 95%. The rewards given by the teacher, including gestures, thumbs-up, objects, recognition, certificates of appreciation, and praise, were able to increase students’ learning interest, as indicated by focused attention, feelings of enjoyment, and willingness to actively engage in learning. The positive impact of reward provision was an increase in students’ motivation and participation. However, negative impacts were also found, such as the emergence of jealousy among students when reward provision was not managed fairly. Based on the results of the analysis, it can be concluded that reward provision has a positive effect on increasing science learning interest among fifth-grade students at SDN 22 Jeppe’e, Tanete Riattang Barat District, Bone Regency.